2020
DOI: 10.3892/ijo.2020.5105
|View full text |Cite
|
Sign up to set email alerts
|

E7 oncoprotein from human papillomavirus 16 alters claudins expression and the sealing of epithelial tight junctions

Abstract: Tight junctions (TJs) are cell-cell adhesion structures frequently altered by oncogenic transformation. In the present study the role of human papillomavirus (HPV) 16 E7 oncoprotein on the sealing of TJs was investigated and also the expression level of claudins in mouse cervix and in epithelial Madin-Darby Canine Kidney (MDCK) cells. It was found that there was reduced expression of claudins-1 and-10 in the cervix of 7-month-old transgenic K14E7 mice treated with 17β-estradiol (E 2), with invasive cancer. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 176 publications
0
4
0
Order By: Relevance
“…The reasons for these phenomena are complex and not fully understood. Similarly, several experimental studies on the role of HPV16 showed that the FVB/N strain is highly sensitive to skin carcinogenesis of mice (Herber et al 1996;Lambert et al 1993), as well as cervical cancer (Uc et al 2020), possibly due to the availability of the E6/E7 proteins in the latter study. To elucidate if the FVB/N genetic background is more suitable for the modulation of the URR11 activity, the mice used in this study were back-crossed from their original B6D2F n genetic background for two generations to FVB/N, resulting of a 75% portion of FVB/N in the genetic pool.…”
Section: Age Of Micementioning
confidence: 80%
See 1 more Smart Citation
“…The reasons for these phenomena are complex and not fully understood. Similarly, several experimental studies on the role of HPV16 showed that the FVB/N strain is highly sensitive to skin carcinogenesis of mice (Herber et al 1996;Lambert et al 1993), as well as cervical cancer (Uc et al 2020), possibly due to the availability of the E6/E7 proteins in the latter study. To elucidate if the FVB/N genetic background is more suitable for the modulation of the URR11 activity, the mice used in this study were back-crossed from their original B6D2F n genetic background for two generations to FVB/N, resulting of a 75% portion of FVB/N in the genetic pool.…”
Section: Age Of Micementioning
confidence: 80%
“…Effect of the genetic background on transgene expression Woodworth et al (2004) and Uc et al (2020) have shown that the FVB/N genetic background might be suitable for studies on human papillomaviruses, as demonstrated by several mouse models with HPV16, as compared to the C57BL/6 or Balb/c genetic backgrounds. Therefore, the URR11-lacZ mice were backcrossed to the FVB/N genetic background.…”
Section: Urr X E2 Driven Reporter-gene Expressionmentioning
confidence: 99%
“…Hence, we analyzed if the absence of ZO-2 altered claudin-4 expression in cells cultured on NRA. We analyzed claudin-4, since previous reports had shown that it is more abundant in MDCK cells, stably expressing E7 oncoprotein from human papillomavirus 16 [ 45 ], and displays an altered pattern of expression in a wide variety of carcinomas (for review, see [ 46 ]). Figure 12 A shows that 24 h after parental and ZO-2 KD cells were plated on NRA, in comparison to the flat surface of coverslips, claudin-4 expression in the cytoplasmic vesicles augmented, both in sparse and confluent cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Researches have clari ed that tight junction might play an import part in HPV-related diseases. E7 oncoprotein from human papillomavirus 16 alters claudins expression and the sealing of epithelial tight junctions, accompanying by a reduced expression of claudins -1, -2 and -10, and an increase in claudin-4 [42]. Additionally, in HPV positive tumor cells, E6-mediated inhibition of MAGI-1 function contributes to HPVinduced malignancy by perturbing tight junction assembly with concomitant stimulation of proliferation and inhibition of apoptosis [43,44].…”
Section: Igf2bp3 Was Related To the Tight Junctions In Hpv-related Cescmentioning
confidence: 99%